Applicability of the ecosystem type approach to model permafrost dynamics across the Alaska North Slope. Issue 1 (6th January 2017) - Nicolsky, D. J.; Romanovsky, V. E.; Panda, S. K.; Marchenko, S. S.; Muskett, R. R
Abstract: Thawing and freezing of Arctic soils is affected by many factors, with air temperature, vegetation, snow accumulation, and soil physical properties and soil moisture among the most important. We enhance the Geophysical Institute Permafrost Laboratory model and develop several high spatial resolution scenarios of changes in permafrost characteristics in the Alaskan Arctic in response to observed and projected climate change. The ground thermal properties of surface vegetation and soil column are upscaled using the Ecosystems of Northern Alaska map and temperature data assimilation from the shallow boreholes across the Alaska North Slope. Soil temperature dynamics are simulated by solving the 1‐D nonlinear heat equation with phase change, while the snow temperature and thickness are simulated by considering the snow accumulation, compaction, and melting processes. The model is verified by comparing with available active layer thickness at the Circumpolar Active Layer Monitoring sites, permafrost temperature, and snow depth records from existing permafrost observatories in the North Slope region. Key Points: We develop scenarios of changes in permafrost characteristics in the Alaskan Arctic in response to projected climate change The ground thermal properties are upscaled using an ecosystems map and data assimilation from the shallow boreholes The model is tested against measured active layer thickness, permafrost temperature, and snow depth records